The Influence of Debt Policy Determinants during the Covid-19 Pandemic in the Tourism, Hotel and Restaurant Sector - Yudha Kusuma; Dwi Harini; Khomsiyah Khomsiyah (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The purpose of this research is to analyze and study Company Size, Tangibility and Business Risk on Debt Policy in Tourism, Hotel and Restaurant companies listed on the IDX in 2017-2021. This type of research is descriptive quantitative. Of the 130 populations, only 90 samples met the criteria. Data processing with multiple linear regression. The results of the partial test are only tangibility which has a positive effect on debt policy, while Company Size has a negative effect on debt policy and Business Risk does not have a positive effect. Simultaneous test results where Company Size, Tangibility and Business Risk affect debt policy with a coefficient of determination of 0.209 which means that 20.9% of variations in debt policy can be explained by variables (company size, tangibility, business risk) where the remaining 79.1% is influenced by factors other.